2016
DOI: 10.1111/echo.13199
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Longitudinal Strain Measures Independently Predict Chronic Heart Failure Mortality

Abstract: The assessment of right ventricular (RV) function still remains a challenge. Two-dimensional (2D) speckle tracking has recently been proposed to evaluate right ventricular function by analyzing myocardial deformation. The aim of this study was to evaluate the role of 2D systolic strain measures of RV in predicting mortality in patients with chronic heart failure (HF). We enrolled 332 outpatients in a stable clinical condition and in conventional therapy. A right ventricular-focused four-chamber view was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 28 publications
4
53
0
Order By: Relevance
“…Previous studies have demonstrated the superior prognostic use of RVFWS compared with TAPSE and other conventional echocardiographic parameters in patients with pulmonary arterial hypertension and other causes of HF. 7,8 The current study by Carluccio et al 4 in HF with reduced ejection fraction (HFrEF) patients with preserved TAPSE adds to this body of evidence, demonstrating RVFWS to be a more discriminating prognostic tool than other echocardiographic measures of RV function in HF patients.…”
Section: Why Might Free Wall Strain Be a Superiormentioning
confidence: 71%
“…Previous studies have demonstrated the superior prognostic use of RVFWS compared with TAPSE and other conventional echocardiographic parameters in patients with pulmonary arterial hypertension and other causes of HF. 7,8 The current study by Carluccio et al 4 in HF with reduced ejection fraction (HFrEF) patients with preserved TAPSE adds to this body of evidence, demonstrating RVFWS to be a more discriminating prognostic tool than other echocardiographic measures of RV function in HF patients.…”
Section: Why Might Free Wall Strain Be a Superiormentioning
confidence: 71%
“…64 Furthermore, RV-GLS showed prognostic relevance when used together with standard indexes of LV function. 65,66 In HF with preserved EF (HFpEF), LV-GLS is able to predict hospital admission rate, cardiovascular mortality, and cardiac arrest, independently from the other clinical predictors. 67 At 3-…”
Section: Prog Nos Ti C Value Of S Tr Ainmentioning
confidence: 99%
“…Primarily developed in the LV, several studies have explored the value of longitudinal shortening of the RV-free wall in patients with advanced HF referred for heart transplant (23) and outpatients with HF (26). The software used for speckle tracking have mainly been developed for the LV.…”
Section: Latest Developments In Echocardiographymentioning
confidence: 99%